THE EFFECT OF TOMAN (Channa micropeltes) FISH EXTRACT ON EPITHELIAL THICKNESS IN DIABETES MELLITUS WOUND HEALING (In Vivo Study on the back of male Wistar rat (Rattus novergicus)) - Nina Audina; Amy Nindia Carabelly; Didit Aspriyanto (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Re-epithelialization is the process of formation of new epithelium which is important in wound healing process, the faster the process then the sooner the process of wound healing. Toman fish (Channa micropeltes) is trusted as an alternative medicine to accelerate wound healing. Toman fish contains albumin which acts an antioxidant. Antioxidant can reduce Reactive Oxygen Species (ROS) which increased at state of hyperglicemia in people with diabetes mellitus (DM), Thus accelerating the process of Re epithelialization on diabetes wound. Purpose: The Purpose of this research was to prove that fish extract Toman dose 16 ml/Kg body weight effect on thickness of the epithelium of Wistar Rat Injuries Induced DM are seen on the 2, 4 and 8 day. Material and methods: This research was true experimental design with posttest-only with control design with complete random design. This research used 27 Wistar rats are divided into 9 treatment groups, Toman fish extract dose 16 mL/Kg BW, Haruan fish extract 13,54 mL/Kg BW, and BR2 feed only. The calculation of epithelial thickness was calculates using the ImageJ software application by measuring histopathological results. Research result: The result of Two way Anova test and Post Hoc LSD test showed that there was a significant difference of effect on group Toman fish extract 16 mL/Kg BW with Haruan fish extract 13,54 mL/Kg BW and BR2 feed only to increase the thickness of the wound of epithelium of Wistar rat Induced DM. Toman fish extract showed the highest mean of epithelial thickness with 2nd day (76,69 µm), 4th day (99,21 µm) and 8th day (124,23 µm). Conclusion: There was effect of Toman fish extract dose 16 mL/Kg BW on increased epithelial thickness of Wistar rats wound on induced diabetes mellitus are seen on the days 2, 4 and 8.